Identification and molecular characterization of a novel varicosa-like virus from red clover - Koloniuk, Igor; Fránová, Jana; Sarkisova, Tatiana; Přibylová, Jaroslava; Lenz, Ondřej; Petrzik, Karel; Špak, Josef (Archives of virology, 2018)
During aetiological study of diseased red clover (Trifolium pratense L.) using high throughput sequencing, a novel virus with a 10 kb genome divided into two segments was discovered. The virus, tentatively named red clover associated varicosavirus (RCaVV), is phylogenetically related to classifiable members of the genus Varicosavirus (family Rhabdoviridae, order Mononegavirales). Analysis of mRNA levels from the individual RCaVV genes suggested possible differences in transcription regulation between rhabdoviruses with divided and undivided genomes.
Keywords: High-Throughput Nucleotide Sequencing; Sequence Analysis, DNA; genom virový; Phylogeny; nemoci rostlin; Genome, Viral; sekvenční analýza DNA; Trifolium; fylogeneze; Plant Viruses; DNA Viruses; DNA viry; rostlinné viry; vysoce účinné nukleotidové sekvenování; Plant Diseases; Viral Proteins; virové proteiny